2018
DOI: 10.1038/s41467-018-03943-0
|View full text |Cite
|
Sign up to set email alerts
|

LRH-1 agonism favours an immune-islet dialogue which protects against diabetes mellitus

Abstract: Type 1 diabetes mellitus (T1DM) is due to the selective destruction of islet beta cells by immune cells. Current therapies focused on repressing the immune attack or stimulating beta cell regeneration still have limited clinical efficacy. Therefore, it is timely to identify innovative targets to dampen the immune process, while promoting beta cell survival and function. Liver receptor homologue-1 (LRH-1) is a nuclear receptor that represses inflammation in digestive organs, and protects pancreatic islets again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
91
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(113 citation statements)
references
References 66 publications
15
91
2
Order By: Relevance
“…While accumulating evidence confirms the anti-inflammatory role of LRH-1/NR5A2 on immune cells through GCs, the expression and function of this NR in such cells have remained scarce. We and others have recently shown that LRH-1/NR5A2 is expressed in macrophages where it plays a pivotal role in promoting the anti-inflammatory M2 phenotype [51,102]. LRH-1/NR5A2 expression was shown to be increased by the Th2 cytokine IL-13 with the subsequent stimulation of PPAR-gamma ligand synthesis and PPAR-gamma activation leading to M2 polarization.…”
Section: Immune Cellsmentioning
confidence: 90%
See 3 more Smart Citations
“…While accumulating evidence confirms the anti-inflammatory role of LRH-1/NR5A2 on immune cells through GCs, the expression and function of this NR in such cells have remained scarce. We and others have recently shown that LRH-1/NR5A2 is expressed in macrophages where it plays a pivotal role in promoting the anti-inflammatory M2 phenotype [51,102]. LRH-1/NR5A2 expression was shown to be increased by the Th2 cytokine IL-13 with the subsequent stimulation of PPAR-gamma ligand synthesis and PPAR-gamma activation leading to M2 polarization.…”
Section: Immune Cellsmentioning
confidence: 90%
“…In recent years, groundbreaking studies have revealed the plasticity of adult alpha-cells to spontaneously reprogram in vivo into insulin-producing cells under extreme beta-cell ablation in mouse pancreas. This alpha-to-beta-cell conversion, normally repressed by insulin and Smoothened-mediated signalling, involves a glucagon/insulin-positive bihormonal cell subpopulation that expresses beta-cell-enriched transcription factors such as MafA, Pdx1 and Nkx6.1 [49][50][51][52]. Consistent with this malleability, ectopic expression of Pax4 or conditional deletion of Arx in mouse alpha-cells led to their conversion into functional insulin-producing cells [53,54].…”
Section: Beta-cell Regeneration Therapiesmentioning
confidence: 93%
See 2 more Smart Citations
“…These results may have direct relevance, as well as having direct applications in biomedicine, to the way processes related to K + equilibria can be controlled in metabolic disorders such as diabetes mellitus . Therefore, the use of the ionophores to modulate transport in live beta cells will open up a new avenue for the creation of useful new drugs.…”
Section: Resultsmentioning
confidence: 97%